Snemanje in arhiviranje ljudske glasbe = Népzene rögzítése és archiválása Strokovni priročnik = Szakmai kézikönyv - Kunej, Rebeka (ZRC SAZU, Založba ZRC, 2020)
The publication focuses on the most important aspects of field research, documentation, archiving and preservation of folk music heritage: it contains elementary guidelines for fieldwork, provides the basics concepts of music and text transcriptions, and draws attention to the correct handling and preservation of unique field material, especially sound and written sources. It is intended to address those who are interested in the discovery and research of folk instrumental and vocal music, to support them with recommendations for their work, and thus to make them aware not only of the importance of discovering and collecting folk music in the field, but also of the importance of preserving documented field material. The bilingual Slovenian-Hungarian handbook Snemanje in arhiviranje ljudske glasbe / Népzene rögzítése és archiválása (Folk Music Recording and Archiving Handbook) is the result of the project "Folk Music Heritage: Exploration, study and dissemination of the common folk music heritage", carried out in the framework of the Interreg V-A Slovenia Hungary cross-border cooperation in the years 2018-2021.